Representation of Family Dysfunction in the Film "Noktah Merah Perkawinan" (Semiotic Analysis of Roland Barthes) - Firda Iga Syahmawaty; Kadek Dristiana Dwivayani; Silviana Purwanti (Jurnal Indonesia Sosial Sains, 2024)
A film is a collection of many images combined into a single whole, consisting of audio and visual components. Movies also often serve as a mirror of social reality. One of the Indonesian films that reflects social reality is the film "Noktah Merah Perkawinan" which tells the story of conflicts and dynamics in domestic life, as well as depicting various social and cultural issues that are relevant to Indonesian society. The purpose of this study is to identify and analyze how family dysfunction is represented in the movie "Noktah Merah Perkakahan" and how this can affect people's perception of family problems. Using a descriptive qualitative research method with Roland Barthes' semiotic analysis by identifying several scenes that describe the characteristics of being in a dysfunctional family proposed by a psychotherapist named Dr. Rashmi Prakash in Fistory Parenting, including lack of communication, lack of empathy, mental problems, excessive behavior control, lack of emotional support and violence. The findings emphasize the depiction of gender inequality as a major contributing factor to dysfunction, revealing that children are deeply impacted by such dynamics. This research enriches the understanding of media's role in portraying family dysfunction and aims to offer insights into addressing such issues effectively in real family settings.